Adubação fosfatada, produção e qualidade de sementes de populações de amendoim - Marubayashi, Oswaldo Massuo [UNESP]; Rosolem, Ciro Antonio; Nakagawa, Joao [UNESP]; Zanotto, Maurício Dutra [UNESP] (My University, 1997)
The objective of this work was to evaluate the response of groundnut (Arachis hypogaea L.) to different doses of phosphate fertilization (0, 40, 80 and 120 kg/ha of P 2O 5) for yield and quality of seeds. Triple-superphosphate (45% of P 2O 5 and 15% of CaO) was used. The groundnut genotypes were: Tatu, Oirã, Tupã, FCA 170 and FCA 265. The dose of 40 kg/ha of P 2O 5 exerced positive influence on yield and quality of seeds. The genotypes showed similar behaviour as for seed production and germination for all doses of phosphorus with interaction between genotypes and P doses as for 100 seeds weight and seed vigor. The dose of 40 kg/ha of P 2O 5 is enough for good production and quality of groundnut.

O objetivo do presente trabalho foi avaliar a resposta do amendoim (Arachis hypogaea L.) a diferentes doses de adubo fosfatado (0, 40, 80 e 120 kg/ha de P2O5), com vistas à produção e qualidade de sementes. Usou-se superfosfato triplo (45% P2O5 e 15% CaO). As populações de amendoim foram: Tatu, Oirã, Tupã, FCA 170 e FCA 265. A dose de 40 kg/ha de P2O5 exerceu influência positiva na produção e qualidade das sementes. As populações de amendoim apresentaram comportamento assemelhado quanto à produção de sementes e sua germinação, em todas as doses de P, mas com interações entre genótipos e doses de P no peso de 100 sementes e no vigor das sementes. A dose de 40 kg/ha de P2O5 é suficiente para boa produção e qualidade do amendoim.
Phosphorus fertilization, yield and quality of seeds in peanut populations
Keywords: Arachis hypogaea; Cultivars; Germination; Phosphorus; Vigor